Analisis kecepatan teknik Front Kicks pada atlet juara dunia pencak silat 2022: Analisis kinematik - Syaifullah, Rony; Lingsir Maghribi, Inosen (Universitas Nusantara PGRI Kediri, 2023)
Pencak silat is the dominant sport using the feet and hands. Kicks in pencak silat require speed to produce points, the faster the kick is made, the more difficult it will be to stop, fend off, or catch. This study aims to describe the difference in front kick speed between two male and female athletes of the Indonesian national team who are the 2022 pencak silat world champions. The research method used in quantitative descriptive research with the subjects of 2022 world champion pencak silat athletes in male and female numbers. This research instrument uses a Fujifilm XT 4 camera with camera placement at a distance of 5 meters from the arena. The video results were analyzed using Kinovea 0.9.4 software by calculating the speed of the subject's Front Kicks. The male sample produced an average speed of 3.25 m/s with an average breakdown of a 1.82-meter kick distance and an average travel time of 0.56 seconds. The female sample produced an average speed of 2.71 m/s with details of an average 1.90-meter kick distance and an average travel time of 0.70 seconds. Future research is expected to examine kinematic parameters in other techniques in pencak silat so that they know more about things that can support the performance of pencak silat athletes.